Otoritarianisme-birokratik orde baru, krisis ekonomi dan politik, dan demokrasi formal masa reformasi - Budi Rajab (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2022)
Since Indonesia’s new order led by Suharto rose to power, many countries have expressed admiration for the New Order (1966 – 1997), including developed countries, as an efficient and effective government, which was able to drastically reduce inflation and maintain economic growth. Previously, during the Old Order (1956-1965), the Indonesian economy stagnated, with very high inflation, even leading to bankruptcy, as well as conflicts between communists and military institutions. With the military institution winning the conflict, the New Order reversed the way of managing the state which in the Old Order era emphasized excessive political interference, so that economic development was neglected. The New Order state tried to build an economy with a capitalist system whose financing relied heavily on foreign debt and investment. foreign. Economic development is bearing fruit, poverty is reduced, education and health of the Indonesian people are better, but the political sector was controlled by the New Order State in a bureaucratic-authoritarian manner, the masses were demobilized strictly and repressively, even coercively. However, three decades later, the New Order regime was faced with an economic crisis in the mid-1990s and civil society movements and other civil groups demanding democratization of the political system. The community movement succeeded in overthrowing the New Order regime and replaced it with a reform regime. Economic development remains a priority of this reform regime in a capitalistic manner, but the democratic political system it develops is still conventional, procedural democracy, not participatory democracy, which means that although it no longer governs repressively, conventional state institutions remain strong, such as the executive, legislative, and the judiciary, while civil society groups are somewhat neglected.